Superparamagnetism Phenomenon for a Mixed Spin Ferrimagnetic Binary System - Ghafel, Aqeel; Mohamad, Hadey K. (University of Thi-Qar Journal of Science, 2024)
A decorated ferrimagnetic mixed triangular system was studied using the molecular mean-field approximation. The outcomes of the investigation were examined using the Blume-Capel Ising model. The study paper investigates the influence of crystal and external magnetic fields on ferrimagnetic devices decorated with mixed spin-2 and spin-7/2 of a triangular lattice. It is noteworthy that spin-2 ions are located at the nodal points, whereas six additional spin-7/2 ions surround the proposed lattice. Altering the exchange interactions through the specific crystal and external magnetic fields induces superparamagnetic behaviours. New characteristics reveal that mixed spin triangular decorated ferrimagnets exhibit superparamagnetic behaviour at DA∕|J2|=-2.5, with J1 = -0.5 and J2 = -1.0 in the range (15 ≤ KBT /|J2| ≤ 18). It is important to note that the total magnetization changes with the external magnetic field and affects the superparamagnetism phenomenon of a decorated mixed spin ferrimagnet when DA/|J2| = 8, and DB/|J2|=-11, J1 = -0.5 and J2 = 1, for KBT/|J2| = 2, 2.5, 3, 3.5, and 4 Ko respectively.